Biofertilizer production in Africa: Current status, factors impeding adoption and strategies for success - Adekunle Raimi; Ashira Roopnarain; Rasheed Adeleke (Scientific African, 2021)
Presently, the global biofertilizer market is expanding due to the rising acceptance of efficient soil nutrient management practices such as the application of biofertilizers amongst farmers. Biofertilizers are preferred to chemical fertilizers because they are cost-effective, ecologically friendly, and guarantee sustainable agricultural production. However, the biofertilizer industry is underdeveloped in many African countries due to several challenges; thus, the full adoption and benefits of biofertilizer are yet to be fully realized compared to the developed nations. Therefore, the present review describes the production, usage, challenges as well as the strategies and opportunities for the development of biofertilizer in Africa. The findings show that inadequate biofertilizer research, lack of technology development, and ineffective regulatory framework have largely contributed to the challenges of biofertilizer development in Africa. Although there is evidence of some form of regulations in some African nations, effective biofertilizer regulations and quality control management championed by the government would further promote the production of quality biofertilizers and usage amongst African farmers. Adequate and effective extension programs, agromarket development, as well as agricultural and research institution development, could improve the production and adoption of biofertilizers in Africa. To achieve increased commercial production and optimal application of biofertilizer amongst farmers in Africa, a deliberate intervention by African government through biofertilizer policy, funding and the development of efficient quality control system and market strategies is essential. More so, government and private sector participation in sustainable investment and technical support will lead to substantial biofertilizer commercialization and adoption in Africa.